2010
DOI: 10.1016/j.jtcvs.2009.08.038
|View full text |Cite
|
Sign up to set email alerts
|

Augmentation of systemic blood pressure during spinal cord ischemia to prevent postoperative paraplegia after aortic surgery in a rabbit model

Abstract: Augmentation of systemic blood pressure during spinal cord ischemia can reduce ischemic insult and postoperative neurologic adverse events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 22 publications
(27 reference statements)
3
22
0
Order By: Relevance
“…The fiber optic probe and monitoring device reliably detected spinal cord responses to pharmacological and physiological interventions; the detected responses were in line with published data 29 . Boluses of hypertensive agents created brief periods of hypertension, which were accompanied by brief increases in spinal cord blood flow and oxygenation.…”
Section: Discussionsupporting
confidence: 85%
“…The fiber optic probe and monitoring device reliably detected spinal cord responses to pharmacological and physiological interventions; the detected responses were in line with published data 29 . Boluses of hypertensive agents created brief periods of hypertension, which were accompanied by brief increases in spinal cord blood flow and oxygenation.…”
Section: Discussionsupporting
confidence: 85%
“…The lower incidence of spinal cord injury after endovascular stent-grafting compared to that after open aortic surgery may be attributed to hemodynamic stability while inserting the graft. 70 On the other hand, we also found that high reperfusion pressure in the same models may be deleterious to the spinal cord. 71 Nowadays, every effort is made to maintain the systemic blood pressure regardless of whether we are reconstructing the intercostal arteries or sacrifi cing them.…”
Section: Effect Of Systemic Blood Pressure On Spinal Perfusionsupporting
confidence: 50%
“…88 described the effect of maintaining high MAP on spinal cord protection in a rabbit model of aortic cross clamping by comparing high and low blood pressure animal groups to a control group; mean (standard deviation) arterial blood pressure during ischemia were controlled at 121.9 (2.8), 50.8 (4.3), and 82.3 (10.7) mmHg in high blood pressure, low blood pressure, and control groups, respectively. They observed higher spinal cord blood flow, lower markers of oxidative stress, faster recovery of transcranial MEPs, and less histological damage of the motor neurons in the animal group treated with higher MAPs.…”
Section: Perioperative Anesthetic Managementmentioning
confidence: 99%